Faktor-faktor yang berhubungan dengan pemanfaatan pelayanan posyandu lansia - Rahman Makaminan; Greta Jane Pauline Wahongan; Martha Marie Kaseke (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The elderly population undergoes an aging process that renders them vulnerable to various physical, mental, and social health issues. As the number of elderly individuals in Indonesia rises, the need for affordable and sustainable healthcare services becomes increasingly critical. One government initiative aimed at improving the health status of the elderly is the implementation of integrated service posts for the elderly. However, the utilization rate of these services remains suboptimal in many areas, including the working area of ​​the Gemeh Community Health Center in Talaud Regency. Purpose: To analyze the relationship between family support, the role of health workers, and attitudes toward the utilization of integrated service posts for the elderly. Method: This study employed a quantitative, cross-sectional design and was conducted in the working area of ​​the Gemeh Community Health Center, Talaud Regency, between February and April 2026. The study population consisted of 600 elderly individuals aged 60–70 years. A sample of 200 respondents was determined using Slovin's formula and selected via simple random sampling. Data collection was carried out using a questionnaire that had undergone validity and reliability testing. Data analysis included univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using multiple logistic regression. Results: This study reveals that 63.3% of respondents utilized the integrated service post for the elderly. The majority of respondents received family support (92%), rated the role of health workers as